Electrochemical sensing of lactate by using an electrode modified with molecularly imprinted polymers, reduced graphene oxide and gold nanoparticles - Pereira, Thulio César [UNESP]; Stradiotto, Nelson Ramos [UNESP] (Springer Nature, 2019)
This paper reports on a sensitive and selective electrochemical sensor for lactic acid. The sensor is based on molecularly imprinted polymers (MIP), obtained on glassy carbon electrode (GCE) modified with reduced graphene oxide and gold nanoparticles. The MIP was obtained by electropolymerization of the o-phenylenediamine (o-PD) on the modified surface of the GCE in the presence of lactic acid. The steps involving the GCE modification and MIP construction were characterized by cyclic voltammetry, electrochemical impedance spectroscopy, scanning electron microscopy and atomic force microscopy. The results were evaluated using differential pulse voltammetry, using the hexacyanoferrate redox system as an electrochemical probe. Under optimized experimental conditions, the imprinted sensor has a linear response in the 0.1 nM to 1.0 nM lactic acid concentration range, with detection limit of 0.09 nM. The sensor exhibits excellent selectivity in the presence of molecules of similar chemical structure. It was applied for the selective determination of lactic acid in sugarcane vinasse. The recovery values ranged from 97.7 to 104.8%. [Figure not available: see fulltext.].
Keywords: Electrochemical sensor; Electropolymerization; Lactic acid; o-Phenylenediamine; Sugarcane vinasse